Environmental determinants of atopic eczema phenotypes in relation to asthma and atopic sensitization - KARADAĞ, BÜLENT TANER (BLACKWELL PUBLISHING, 2007)
Background: There is still uncertainty about the determinants of atopic eczema (AE). To explain the heterogeneity of the disease, different phenotypes of AE have been suggested. Methods: The cross-sectional PARSIFAL study included 14 893 school-age children of farmers or children attending Steiner schools and their respective reference groups. A detailed questionnaire was completed, and house dust was collected for the measurement of endotoxin and glucans. Atopic sensitization was defined by allergen-specific IgE levels in the serum. Results: In multivariate analyses, helping with haying was the only variable related to a farming environment having a consistent inverse association with both current symptoms and a doctor's diagnosis of AE [aOR = 0.65 (95% CI: 0.46-0.93) and 0.73 (0.51-1.05)], respectively. Severe lower respiratory tract infections (LRTI) in the first 2 years of life and usage of antibiotics ever were found to be positively related only to asthma-associated AE, whereas the effect of LRTI on AE without asthma had an opposite effect. Levels of beta(1 -> 3)-glucans in mattress dust were inversely related to a doctor's diagnosis of asthma-associated AE [aOR = 0.75 (0.57-0.98)], and endotoxin levels to current symptoms of asthma-associated AE [aOR = 0.73 (0.57-0.94)]. Conclusions: The analyses of the PARSIFAL study revealed two different phenotypes of AE, depending on the association with asthma and wheezing ever. With regard to the hygiene hypothesis, help with haying, exposure to beta(1 -> 3)-glucans and endotoxin were found to be inversely associated with the AE phenotype associated with asthma and wheezing.
Keywords: atopic eczema; children; endotoxin; beta(1 -> 3)-glucans; PLACEBO-CONTROLLED TRIAL; HOUSE-DUST; ALLERGIC SENSITIZATION; DERMATITIS; CHILDREN; ASSOCIATION; PROBIOTICS; EXPOSURE; LIFE; POLYMORPHISMS